A Guide to Assessing Needs : Essential Tools for Collecting Information, Making Decisions, and Achieving Development Results - Watkins, Ryan (World Bank, 2012)
This book will benefit people and teams involved in planning and decision making. On the basis of their pragmatic value in guiding decisions, needs assessments are used in various professions and settings from emergency rooms to corporate boardrooms to guide decision making. Nonetheless, although needs assessments have many different applications, in this book on needs assessments as they are applied in organizations to accomplish results, as opposed to their use in personal decisions or medical triage. This book, in turn, is guide to assessing needs and then making essential decisions about what to do next. This book filled with practical strategies, tools, and guides covers both large-scale, formal needs assessments and less-formal assessments that guide daily decisions. Included in the book is a blend of rigorous methods and realistic tools that can help make informed and reasoned decisions. Together, these methods and tools offer a comprehensive, yet realistic, approach to identifying needs and selecting among alternative ways as go forward. Sections one and two offer quick, yet full, answers to many frequently asked questions regarding how to make justifiable decisions. Next, section three examines a variety of tools and techniques that can be used for both collecting information and making decisions. Appendix A then offers a number of checklists and guides for managing the systematic assessment processes that lead to quality decisions. Finally, the reference list at the end of the book is a valuable resource to research, tools, and discussions of needs assessment.